Bibliometrik Analysis: Pembelajaran Speaking Session Menggunakan Instagram Pada Data Base Scopus 2014-2024 - Riri Narasati; Ahmad Faqih; Dadang Sudrajat (Prosiding SISFOTEK, 2024)
In today's digital age, social media plays an important role in various aspects of life, including education. This research explores the use of Instagram as a learning tool to improve English speaking skills. Through bibliometric analysis, this study identifies previous research trends and evaluates the effectiveness of Instagram-based learning methods. It also reviews existing literature to understand how Instagram has been used in language learning contexts, as well as identifying existing research gaps. The results show that the use of Instagram in English language learning can increase student motivation and participation. Interaction through video, story and dialog-based content on Instagram proved effective in improving speaking skills. The study also found that the use of project-based tasks on Instagram can help students in developing their confidence and speaking ability. In addition, this study highlights the importance of structured guidance and feedback in maximizing the benefits of learning through Instagram. This research makes a novel contribution to the literature by offering a more in-depth approach to the use of Instagram in English language learning. By exploring effective learning strategies and their impact on students' speaking skills, this study explores the role of Instagram in English language learning.